2019
DOI: 10.1155/2019/4231764
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarette Burns: A Case Report and Review of Current Literature

Abstract: Due to the development of electronic cigarettes and their use in our patient population, this article seeks to evaluate the safety and associated morbidity that may result from their use. This article also presents a patient case regarding an explosion of an electronic cigarette battery and the resultant injury and deformity that occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The majority of injuries were caused due to explosion (82/126), including 48 assembled devices [21,, 20 self-exploded batteries [95,97,102,111,112,[115][116][117] and 14 without specifying [118]. Second most common injury was thermal burns (24/126) caused by 14 self-combusted batteries [21,111,115,[119][120][121][122], 6 self-combusted assembled devices [115,120,123,124], 2 exploding devices [99,102], 1 in-pocket e-cigarette self-activation [125] and 1 case for which the ignition was induced by a motorcycle crash [111]. A combination of explosion and thermal burn caused by the explosion of the assembled device (7/126) [21,112,120,126,127] was the 3rd most common cause of injury.…”
Section: Traumatic Injurymentioning
confidence: 99%
“…The majority of injuries were caused due to explosion (82/126), including 48 assembled devices [21,, 20 self-exploded batteries [95,97,102,111,112,[115][116][117] and 14 without specifying [118]. Second most common injury was thermal burns (24/126) caused by 14 self-combusted batteries [21,111,115,[119][120][121][122], 6 self-combusted assembled devices [115,120,123,124], 2 exploding devices [99,102], 1 in-pocket e-cigarette self-activation [125] and 1 case for which the ignition was induced by a motorcycle crash [111]. A combination of explosion and thermal burn caused by the explosion of the assembled device (7/126) [21,112,120,126,127] was the 3rd most common cause of injury.…”
Section: Traumatic Injurymentioning
confidence: 99%
“…Our search yielded 18 case reports and 23 case series, adding up to a total of 180 cases, published between 2016 and 2020 in a variety of medical journals. 7,8,18,25, The incidents took place in the United States, the United Kingdom, Canada, Germany, France, Belgium, and Malaysia. To our knowledge, this is the most extensive review on this topic, as all kinds of traumatic injuries were included in contrast to other systematic reviews limited to burn injuries.…”
Section: Resultsmentioning
confidence: 99%
“…11,15,16 The potential toxicity of ENDS vapor and its potential for increasing tobacco use have also been addressed. [17][18][19][20][21] In 2016, Madsen et al 22 published a case report suggesting that ENDSs can induce inflammation and mimic responses found in metastatic cancer. One year later, Fracol et al 23 found EC vapor to be cytotoxic to endothelial cells, independently of nicotine content.…”
mentioning
confidence: 99%
See 1 more Smart Citation